PENGARUH ELECTRONIC WORD OF MOUTH DAN PERCEIVED RISK TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN TOKOPEDIA - Ramadhani, Ritma; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2019)
The purpose of this study is to determine the effect of electronic word of mouth (e-WOM) and perceived risk to the purchasing decision at Tokopedia. This type of research is explanatory research. Sampling technique using nonprobability with purposive technique. The number of samples taken as many as 100 respondents, which are the consumer of Tokopedia. In this study assisted by IBM SPSS 21.0 system. The results showed that electronic word of mouth (e-WOM) influences the purchasing decision by contributing 24.4% while the rest is influenced by factors other than e-WOM. Perceived risk influences the purchasing decision by contributing 26.8% while the rest is influenced by factors other than perceived risk. Meanwhile, simultaneously electronic word of mouth (e-WOM) and perceived risk influence to purchasing decision by donating 33.3% while the rest influenced by factors other than electronic word of mouth (e-WOM) and perceived risk. Based on the calculation of Test F shows that there is a significant influence between electronic word of mouth (e-WOM) and perceived risk to the purchasing decision. This means the better electronic word of mouth (e-WOM) and perceived risk, the higher the purchasing decision at Tokopedia. Suggestions in this research is Tokopedia must encourage its consumers to write a more complete and clear review by providing reward points and also for Tokopedia to improve its services and provide education about the transaction mechanism so that consumers have a good risk perception towards Tokopedia.